TYTA LIWIUSZA DZIEJE RZYMSKIE HRABIEGO OSSOLIŃSKIEGO. PIERWSZY POLSKI PRZEKŁAD AB URBE CONDITA - Agnieszka Dziuba (In Gremium. Studies in History, Culture and Politics, 2018)
This article is devoted to the first, incomplete, Polish translation of Livy’s Ab Urbe condita. The translation was done by the blind count Józef Maksymilian Ossoliński, alumnus of Jesuitic Collegium Nobilium in Warsaw. Considering the comments in the preface directed to a reader, the translator appears to be a mindful person aware of difficulties of his work. Nevertheless, his ‘translatoric operations’ fully coincide with the translation theory. The comparative analysis of the three arbitrarily chosen excerpts of Livy’s Ab Urbe condita shows the weak points of translators craft, which are: an overuse of archaic words, building too long sentences, using flowery metaphors. Although, the translation itself doesn’t live up to the modern translatoric standards, it is important to acknowledge the validity of Ossoliński’s work. As he writes in the preface, Polish historians aim was to fight for a restitution and preservation of a language purity. Through his translation Ossoliński wanted to show the richness and beauty of Polish language to his readers.